Financial autonomy, institutional reform, and irrigation performance - Svendsen, Mark (SAGE Publications, 1994)
There is increasing interest in privatization as a solution to the problem of ineffective and excessively costly irrigation system operations. In this paper by Mark Svendsen, two organizational models showing promise in this regard are examined and compared: the irrigation district model, in which a voluntary association is responsible for system management, and the parastatal model, in which a semi-autonomous government body takes on this responsibility. These two models are represented by a pair of case studies drawn from the United States and the Philippines.